Genetically determined vitamin D reception in metabolically unhealthy obesity in children - A. Abaturov; A. Nikulina (Zaslavsky O.Yu., 2023)
Background. Genomic effects of vitamin D are determined by conformational changes in the structure of the vitamin D receptor (VDR) determined by single nucleotide variants (SNV) of the VDR gene. The purpose is to study the association of the SNV of the VDR gene with metabolically unhealthy obesity (MUO) in children. Materials and methods. Two hundred and fifty-two obese children aged 6-18 years were examined. The main group (n = 152) was represented by patients with MUO. The control group (n = 100) consisted of children with metabolically healthy obesity. Whole genome sequencing (CeGat, Germany) was performed in 31 children of the main group and 21 controls. The level of serum 25-hydroxyvitamin D (Synevo, Ukraine) was measured in all patients. To verify the results, Spearman's correlation coefficient (r) and p-value for each variable were calculated. Results. Five SNVs of the VDR gene were identified: rs2228570 (1 DNA copy number variation (CNV): c.2T>C in 94.23 %); rs731236 (2 CNV: c.11056T>C, c.1206T>C in 65.38 %); rs10783218 (2 CNV: c.296+8C>T, c.146+8C>T in 7.69 %); rs2228572 (2 CNV: c.57C>T, c.207C>T in 1.92 %); rs12721365 (2 CNV: c.1059C>T, c.909C>T in 1.92 % of patients). A correlation between SNV VDR and MUO was observed in the following genotypes: AA rs12721365 (r = 0.21), AA rs2228572 (r = 0.21), GG SNV rs731236 (r = -0.15) and GG rs2228570 (r = -0.31), p < 0.05. Conclusions. The genotypes AG SNV VDR rs12721365, rs2228572 are highly associated with the development of MUO.